PENGARUH SUBTITUSI SLAG BAJA TERHADAP KUAT TARIK BELAH DAN PERMEABILITAS BETON POROUS (PERVIOUS CONCRETE) - Sukarman; Erlina Yanuarini; Andi Indianto; Ryan Anggriawan (Universitas Widyatama, 2022)
Abstract Problems related to road damage are currently growing. Damages that occur are often caused by waterlogging. One of the efforts that can be done is by applying the use of porous concrete. Porous concrete can reduce water runoff and increase infiltration in the soil because it has a high porosity. As a substitute material, steel slag can be an alternative in replacing coarse aggregate. Steel slag is an abundant waste from steel production industrial companies. Currently, steel slag is widely used in high-strength concrete mixes. This study of porous concrete generally refers to ACI 522R 10. The purpose of this study was to analyze the effect of steel slag substitution on the tensile strength and permeability of porous concrete. This experimental study used two variations of the w/c (0.25 and 0.30) with two variations of crushed stone aggregate and steel slag with a diameter of 10 mm-20 mm. The tensile strength and permeability specimen of porous concrete is in the form of a concrete cylinder (15 cm diameter, 30 cm height) with 3 samples of each variation. The tests were carried out at the age of 28 days. Based on the experimental results on porous concrete with steel slag or crushed stone, the value of the tensile strength of concrete with w/c 0.30 is higher than w/c 0.25. Meanwhile, the permeability value of porous concrete in both the mixed variant of steel slag and crushed stone with w/c 0.25 is higher than w/c 0.30. So that the relationship of the tensile strength of concrete is inversely proportional to the value of the permeability of the concrete in the conditions of the two w/c (0.25 and 0.30). Keywords : porous concrete, tensile strength, permeability